Effects of Temperature on Lifespan of Drosophila melanogaster from Different Genetic Backgrounds: Links between Metabolic Rate and Longevity - Mateusz Mołoń; Jan Dampc; Monika Kula-Maximenko; Jacek Zebrowski; Agnieszka Mołoń; Ralph Dobler; Roma Durak; Andrzej Skoczowski (Insects, 2020)
Despite many studies of the aging process, questions about key factors ensuring longevity have not yet found clear answers. Temperature seems to be one of the most important factors regulating lifespan. However, the genetic background may also play a key role in determining longevity. The aim of this study was to investigate the relationship between the temperature, genetic background (fruit fly origin), and metabolic rate on lifespan. Experiments were performed with the use of the wild type Drosophila melanogaster fruit flies originating from Australia, Canada, and Benin and the reference OregonR strain. The metabolic rate of D. melanogaster was measured at 20 °C, 25 °C, and 28 °C in an isothermal calorimeter. We found a strong negative relationship between the total heat flow and longevity. A high metabolic rate leads to increased aging in males and females in all strains. Furthermore, our results showed that temperature has a significant effect on fecundity and body weight. We also showed the usefulness of the isothermal calorimetry method to study the effect of environmental stress conditions on the metabolic activity of insects. This may be particularly important for the forecasting of impact of global warming on metabolic activity and lifespan of various insects.